(untitled) (Research, Society and Development, 2022)
Butia is a native genus from South America, belonging to the Arecaceae family. Known and approached by science for a long time, the objective of this work is to discuss the history of the taxonomy of the genus by perspective of various authors who approached it in their studies. For the review about the genus, different databases were consulted, such as: SciELO, PubMed, Catalog of Theses and Dissertations - CAPES, Brazilian Digital Library of Theses and Dissertations, Palmweb Palms of the World Online, researchgate.net, scholar.google e archive.org. The following descriptors were used: Arecaceae, Butia, Syagrus, Geographical distribution and Arecaceae/Palmae fossil record, in Portuguese and English. Although well established, the genus has undergone several taxonomic changes, resulting in divergences between numbers and species nomenclatures, due to the morphological variations found between them, depending on the stage of plant development, the soil, climate and altitude where they occur, causing confusion even among specialists, which are detailed through this literature review. Although the solid base of knowledge about the genus that we focus on this work be very visible, when we focus on the species level, we realize that the majority of them do not present studies that explore beyond the work of species descriptions, making the group little studied when compared to other genera of angiosperms, mainly about natural hybrids, indicating that there is still much to explore about this genus and the species that compose it.